ENSURING DEEP AND CONTINUOUS KNOWLEDGE ACQUISITION AMONG EVENING EDUCATION STUDENTS THROUGH INTEGRATED TEACHING (PHENOMENON-BASED LEARNING) IN HIGHER EDUCATION BASED ON THE EXPERIENCE OF THE FINNISH EDUCATION SYSTEM (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis analyzes the content, pedagogical potential, and significance of the phenomenon-based learning approach implemented in the Finnish education system, particularly within the context of evening education. This approach involves teaching different subjects in an integrated manner based on a unified theme, thereby contributing to students’ deep and continuous acquisition of knowledge. In Finnish educational practice, one of the key factors contributing to educational effectiveness is the principle that students do not proceed to the next stage until the current topic has been fully mastered.
Keywords: Phenomenon-based learning, integrated teaching, Finnish education system, interdisciplinary integration, evening education, deep and continuous knowledge acquisition, educational effectiveness, pedagogical innovations, educational technologies.